Postcolonialism and the Native American Experience: A Theoretical Perspective - Tripathy, Indian Institute of Technology, Madras, India, Jyotirmaya (Asiatic: IIUM Journal of English Language and Literature, 2009)
Taking the common understanding of â€œpostcolonial as independenceâ€ to task, the presentÂ paper challenges some of the fundamental assumptions circulating in the field at a theoreticalÂ level, and pleads for a radical overhauling of the postcolonial project to accommodate theÂ indigenous peoplesâ€™ cultural resistance in the postcolonial framework. While doing so, itÂ destabilises the very idea of a postcolonial settler literature, thereby placing it in the colonialÂ discourse. By using native American culture as a prototype of postcolonial experience, theÂ paper argues for the restoration of indigenous cultural practices, and then turns them into aÂ critique of Western civilisational complexes. The attempt then is made to locate the agenda ofÂ postcolonialism in the narratives of resistance where decolonisation of mind and history isÂ realised.